DNA damage response(DDR): a link between cellular senescence and human cytomegalovirus - Xinna Wu; Xuqiang Zhou; Sanying Wang; Genxiang Mao (Virology Journal, 2023)
Abstract The DNA damage response (DDR) is a signaling cascade that is triggered by DNA damage, involving the halting of cell cycle progression and repair. It is a key event leading to senescence, which is characterized by irreversible cell cycle arrest and the senescence-associated secretory phenotype (SASP) that includes the expression of inflammatory cytokines. Human cytomegalovirus (HCMV) is a ubiquitous pathogen that plays an important role in the senescence process. It has been established that DDR is necessary for HCMV to replicate effectively. This paper reviews the relationship between DDR, cellular senescence, and HCMV, providing new sights for virus-induced senescence (VIS).